The extent to which the Kitab al-Tawhid 2 course for the second year of secondary school includes the standards of the Education and Training Evaluation Commission - Al-Harbi, AbdulMohsen Abdullah; Abanmi, Fahd AbdulAziz (Journal of Curriculum and Teaching Methodology, 2025)
The main objective of the study was to identify the extent to which the Tawheed Book (2) curriculum for the second secondary grade includes the standards of the Education and Training Evaluation Commission. To achieve the study objectives, the study followed the descriptive analytical approach. The study tool was a content analysis card for the Tawheed Book 2 curriculum for the second secondary grade in light of reviewing the Islamic Education Learning Field Standards document issued by the Education and Training Evaluation Commission, which included (3) axes and a number of standards and indicators. The study reached the following results, the most prominent of which are: The Tawheed Book 2 curriculum for the second secondary grade included content standards indicators at a rate of (35.18%), performance standards indicators at a rate of (31.34%), and common dimensions standards indicators at a rate of (33.47%). Based on the results of the study, the most prominent recommendations and suggestions were: Including the Tawheed Book 2 curriculum for the second secondary grade with topics that discuss the approach of the Sunnis and the community in the unification of names and attributes, including Tawheed Book 2 for the second secondary grade - Sharia track with topics that enhance positive interaction with the universe, life and humanity, holding educational workshops and meetings that would raise the awareness of teachers of Sharia sciences of the importance of the standards issued by the Evaluation Commission. Education and Training.
Keywords: Secondary Stage; Standards; Tawhid Curriculum